Gamma Knife radiosurgery for glossopharyngeal neuralgia: A study of 21 patients with long-term follow-up. (March 2018) - Borius, Pierre-Yves; Tuleasca, Constantin; Muraciole, Xavier; Negretti, Laura; Schiappacasse, Luis; Dorenlot, Antoine; Marguet, Maud; Zeverino, Michele; Donnet, Anne; Levivier, Marc; Regis, Jean
Objective: Glossopharyngeal neuralgia (GPN) is a very rare condition, affecting the patient's quality of life. We report our experience in drug-resistant, idiopathic GPN, treated with Gamma Knife radiosurgery (GKRS), in terms of safety and efficiency, on a very long-term basis. Methods: The study was opened, self-controlled, non-comparative and bicentric (Marseille and Lausanne University Hospitals). Patients treated with GKRS between 2003 and 2015 (models C, 4C and Perfexion) were included. A single 4-mm isocentre was positioned in the cisternal portion of the glossopharyngeal nerve, with a targeting based both on magnetic resonance imaging (MRI) and computed tomography (CT). The mean maximal dose delivered was 81.4 ± 6.7 Gy (median = 85 Gy, range = 60–90 Gy at the 100% isodose line). Results: Twenty-one patients (11 women, 10 men) benefited from 25 procedures. The mean follow-up period was 5.2 ± 3 years (range = 0.9–12.1 years). Seventeen (81%) were initially pain-free after GKRS. At three months, six months and one year after radiosurgery, the percentage of patients with good outcome (BNI classes I to IIIA) was 87.6%, 100% and 81.8%, respectively. Ten cases (58.8%) from the initial pain-free ones had a recurrence, after a mean period of 13.6 ± 10.4 months (range = 3.1–36.6 months). Only three patients (14.2%) had recurrences (two for each one of them) requiring further surgeries. Three patients underwent a second GKRS procedure; one case needed a third GKRS. The former procedures were performed at 7, 17, 19 and 30 months after the first one, respectively. Furthermore, two patients needed additional interventions. At last follow-up, 17 cases (80.9%) were still pain-free without medication. The actuarial pain relief without new surgery was 83%. A transient complication (paraesthesia of the edge of the tongue) was seen in one case (4.8%). Conclusion: GKRS is a valuable, minimally invasive, surgical alternative for idiopathic GPN, with a very high short- and long-term efficacy and without permanent complications. A quality imaging, including T2 CISS/Fiesta MRI and bone CT acquisitions for good visualisation of the nerve and the other bony anatomic landmarks, is essential for targeting accuracy and successful therapy.